Remediating toxic elements with sunflower, hemp, castor bean, & bamboo: an open dataset of harmonized variables - Hyunji Ha; Ken G. Sweat; Kendra D. Conrow; Richard S. Haney; Thomas M. Cahill; David S. LeBauer; Maxwell C. K. Leung (Scientific Data)
Abstract This dataset was compiled between August 1, 2022, and March 15, 2023, through a comprehensive literature review of 587 studies on the uptake of elements from the soil by plants (i.e., phytoremediation). As a proof of concept, we compiled research results on four commodity crops suitable for phytoremediation in semi-arid environments, namely sunflower, hemp, castor bean, and bamboo. Two hundred thirty-eight studies had data on soil types, elemental pollution, and plant components for calculating bioconcentration factors. Using a harmonized set of variables, we extracted data from these studies to create a database to organize results for interpretation and enable consistent and further literature analysis. This approach can help industry experts and environmental researchers select crops for their intended extraction applications, as well as provide insights into the bioaccumulation of toxic elements in plants.